FISHERY RESOURCES AND THE DEVELOPMENT OF AQUACULTURE: INSIGHTS FOR AGRICULTURE HIGHER EDUCATION - Uchola, B. E.; Ati, O. F. (UDS International Journal of Development, 2025)
An investigation was conducted on the capture fisheries and aquaculture subsectors so as to understand their production outputs and characteristics. Estimates of notable fish resources, total number of species (TNS), effective number of species (ENS), global fish production (GFP), capture fisheries production (CFP) and aquaculture production (AP) for 4-decades were retrieved and analyzed. Capture fisheries and aquaculture were characterized using these criteria: mode of production, place of production, management approaches, motivation/goals, and property regimes. Fishery resources remained fairly constant (1000), TNS increased progressively (157 to 438), ENS fluctuated almost regularly and GFP increased in million metric tonnes (MT) steadily (90.6 to 172.8MT). Contributions to annual GFP by CFP steadily decreased (87.1 to 54.0%) while those of AP increased steadily (12.9 to 46.0%). Capture fisheries and Aquaculture are similar in terms of their contributions to food security through the provision of fish. Contribution of fishery resources to global fish production declines as a result of the steady increases from aquaculture.Â  Aquaculture has developed as a culture-based activity. On the basis of culture-based characteristics, aquaculture can exist as either an independent academic discipline in Agriculture universities or an integral unit of existing livestock-based department. Keywords: Farming, Fishing, Fish Production, Education Reforms, Universities